El Excentrico, 1970-10-5 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
October 5, 1970 [5 de octubre de 1970]. No volume or issue number. Cover has a photograph of a bride and groom with the headline, "The former Marina Flores now Mrs. Manuel J. Fernandez [/] September 12, 1970."